2006
DOI: 10.1186/1475-2891-5-12
|View full text |Cite
|
Sign up to set email alerts
|

Soy protein supplementation does not cause lymphocytopenia in postmenopausal women

Abstract: Background: The health benefits of soy isoflavones have been widely investigated; however, there are some concerns as to whether soy isoflavones, similar to ipriflavone, a synthetic isoflavone, cause lymphocytopenia in postmenopausal women. Hence, the purpose of this study was to investigate the extent to which 12-month supplementation of 25 g soy protein containing 60 mg isoflavones alters lymphocyte counts or other hematological parameters in postmenopausal women who were not on hormone replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Lymphocytopenia has been shown in postmenopausal women who received a synthetic isoflavone for three years in a multicenter study [ 34 ]. However, a recent study found that isoflavone for one year did not alter lymphocyte counts in postmenopausal women [ 35 ]. Thus, the impact of HSCs and lymphopoiesis by plant components of isoflavoneor phytosterols remains to be solved.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytopenia has been shown in postmenopausal women who received a synthetic isoflavone for three years in a multicenter study [ 34 ]. However, a recent study found that isoflavone for one year did not alter lymphocyte counts in postmenopausal women [ 35 ]. Thus, the impact of HSCs and lymphopoiesis by plant components of isoflavoneor phytosterols remains to be solved.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Sridhar et al(2010) attributed the decrease in Hb to iron deficiency or to hemolytic or myelopathic conditions. The cause behind the increase in RDW% may be the increased immature RBCs or reticulocyte number (Soung et al, 2006).Free radicals can directly damage red blood cell membranes by peroxidation of membrane polyunsaturated fatty acids (Catala, 2009).It has been shown that thrombocytopenia in cancer patients is accompanied by anemia or leucopenia (Piatek and Akhtari, 2015).In the same concern, Akinbami et al (2013) reported that BC patients had lower MCV, MCH and MCHC values and higher RDW than control.…”
Section: Results In Tablementioning
confidence: 99%
“…These results were similar to the results of Ishimi et al (1999), who showed that an intake of isoflavones in ovariectomized rats improved haematological parameters [ 47 ]. Soung et al (2006) also observed that an intake of soy products in postmenopausal women had a beneficial effect on some haematological parameters [ 48 ] and that isoflavones may affect immune system functioning as a result of their receptors on lymphocytes [ 49 ].…”
Section: Discussionmentioning
confidence: 99%